The role of community colleges in economic development: a case study of internal and external stakeholders’ perceptions - Ramont, John Raymond (Kansas State University, 2022)
Communities strive to grow economically to improve the quality of life of their citizens. Community colleges have long been a key driver of local economic development through education and workforce development programs. Over the past few decades, community colleges have increased their involvement in economic development activities beyond their traditional roles. Some believe the expansion of the role of community colleges to be a natural extension of their mission, while others are concerned this expansion may divert scarce resources into activities that dilute their core mission. Advances in technology, especially in the areas of artificial intelligence and automation, threaten to displace workers at an ever-increasing pace. Additionally, changing technology will require skilled technical workers to constantly retrain throughout their careers. Most studies examining the role of community colleges in economic development tend to focus on direct economic impacts: total payroll, purchasing, and support costs. Few studies have explored how community colleges work within their local regions to drive growth and expand the economy. Therefore, the purpose of this study was to explore the perceptions of internal and external stakeholders of the role of the community college in regional economic development activities, and to identify areas of agreement and gaps in the alignment of perceptions of the various internal and external stakeholders. Research in this area is important to better understand where interaction and support between interdependent actors can be optimized to produce more effective outcomes for economic development efforts through better alignment of resources. The study methodology used a qualitative case study approach examining the perceptions of internal and external stakeholders within a community college service area. The primary data collection method was semistructured interviews with twenty key stakeholders, both internal and external to the organization. Additional data was gathered from economic development plans and documents from the communities in the region to determine whether or not there was a cohesive vision in the region for economic development for the college to align its activities to. The study utilized three theoretical frameworks: Isenberg’s (2014) entrepreneurial ecosystems, Emery and Flora’s (2006) community capitals, and Florida’s (2014) creative class theories. Each framework provided a means to assess the community context for the study. The results of the study indicated the local college is highly regarded in the community, and many of the programs of the college are perceived to be effective. At the same time, both internal and external stakeholders perceived significant room for improvement. Additionally, the study found evidence suggesting structures within the region for supporting strong economic growth are not ideal, and there is a lack of cohesion among the local communities for developing a vision for economic development. Recommendations for practitioners are presented for consideration in cultivating improved conditions to spur economic growth and better align resources and activities to increase the effectiveness of programs and strengthen the role of community colleges. Expanding this research may increase understanding of how colleges effectively integrate within their communities to spur economic growth and prosperity.
Keywords: Role of community colleges in economic development; Entrepreneurial ecosystems; Workforce development